WISE USE OF NATURE - B.Mambetkarimov (Journal of new century innovations, 2024)
Abstract: As we noted in the article, the greatest danger in the biosphere today is the threat of global warming. The cause of global warming is an anthropogenic factor. It has been analyzed that the increase in the amount of gases released into the atmosphere due to the increase of people on the globe and their improper use of natural resources for their own needs is considered a global problem.